Your strong, sexy pregnancy a yoga and fitness plan - Bartlett, Desi (Champaign, IL Human Kinetics, 2020)
Feel confident and capable as a mom-to-be with Your Strong, Sexy Pregnancy: A Yoga and Fitness Plan. Desi Bartlett, founder of the popular Mothers Into Living Fit Program, guides you through your pregnancy. You will feel great in your own body, have the strength to deliver your baby, and recover quickly. With the 3+1 Total Body Fitness philosophy, Bartlett combines yoga, resistance training, cardiovascular training, and nutrition. Personal and practical, her program will help you maintain a strong and healthy lifestyle that benefits you and your baby. Inside you will find the following: over 100 exercises and yoga poses to improve posture, increase flexibility, and relieve low back pain and tension through your body; 16 ready-to-use practices for various stages of pregnancy; techniques to nurture your mental well-being and help manage the emotional highs and lows of pregnancy and motherhood; Desi's tips and advice, including features like Mommy Move, Information No One Tells You, Love-Your-Baby Visualization, and Fun Foods. A truly fit, confident mom is created from the inside out. Let Your Strong, Sexy Pregnancy teach you of how to prioritize your health and happiness. Cultivate your inner power and be a fierce, strong, sexy mom!
Strong is the new skinny -- 3+1 total body fitness -- Mama knows best -- First trimester: increase endurance -- Second trimester: build strength -- Third trimester: prepare to push -- happy birth day! -- New mama recovery workout -- Mommy and me -- Belly blaster series -- Self-care for moms -- Insights for moms over 40
Includes bibliographical references (pages 277-278)
Keywords: Exercise for pregnant women; Yoga